Barnāmaj Ta’līm Al-Lughah Al-‘Arabiyyah fi Mu`assasah Al-Ma’had Al-Islāmiy Miftāh Al-‘Ulūm Al-Yāsīnī Pasūruwān (`Idārah Tākhtītihi) - Ramadhani Rahmatillah; Durrotus Tsaminah; Zakiyah Arifa; Mohd. Jaisar Raju (al Mahāra: Jurnal Pendidikan Bahasa Arab, 2022)
Every educational institution is increasingly improving its quality as the Al-Yasini Islamic Institute Foundation Pasuruan with program in the Foreign Language Development Foundation (LPBA) that existsand continues forward along with other international institutions. This research had three purposes which are to know: 1) the arabic language planning model that are using at LPBA Al-Yasini; 2) the elements in planning the program; 3) the planning process of it’sprogram. The research method is evaluative analysis withinformation from interview, obervation, and documentation. Collected data are analyzed through three activities which are data collection, data reduction, data presentation, and conclusion. The research results are: 1) Planning of the program uses the Long Range Planning type in micro amount with repeated use and Hybrid Planning process; 2) The planning included all the elements except the control element; 3) The planning program include in every step of the education program except the advanced planning step. Moreover, the research stresses to provide its planning by completing the monitoring component and implementing the planning human resources such as directives for teachers until the program implementation is in accordance with planning and achieving goals effectively. Keywords: Management, Program Planning, Arabic Teaching ملخص إن معظم المؤسسات التعليمية متزايد في تحسين جودة التعليم الذي تطوره كمعهدالياسيني فاسوروانالذي يكون معهدا تقليديا أو سلافيا يتمسك لفترة طويلة ببرنامجهفي مؤسسة تطوير اللغات الأجنبية (Lembaga Pengembangan Bahasa Asing/LPBA)ويستمر قدمًا جنبًا مع المؤسسات الدولية الأخرى. وهذ البحث ثلاثة الأهداف: 1)لمعرفة نموذج التخطيط المستخدم في تخطيط برنامج تعليم اللغة العربية فيLPBA Al-Yasini؛ 2)لمعرفة عناصر في تخطيط برنامج تعليم اللغة العربية فيه 3) لمعرفة عملية تخطيط برنامج تعليم اللغة العربية فيه. ونهجه تحيلل تقويمي ومكانه فيLPBA Al-Yasiniبأن يكون مصداره الوثائق المعهدية ومدير المعهد مع موظفيه ومتعلمين فيه.وكان البيانات تجمع بأسلوب المقابلة والملاحظة والتوثيق وطريقة تحليل البيانات المستخدمة هي جمع البيانات وتقليلها وعرضها ثم استخلاص البحث في آخره. ونتائج البحث هي: 1) التخطيط يستخدم مدخل القوىالبشرية بالاستخدام المكرر، ونوعه تخطيط على المدىالمتوسط (Intermediate Planning) بالمقدار الصغير (micro) وتعتمد عمليته على التخطيط الهجين (Hybrid Planning)؛2) التخطيط قد اشتمل على جميع العناصر إلا عنصر المراقبة؛ 3) عمليته لايجري بمرحلة تخطيط لتخطيط. والاقتراحات للبرنامج أن يزود على تحسين تخطيطه باستكمال عنصر المراقبة ومرحلة تخطيط لتخطيط فيه وتنفيذ التخطيط المتعلق بالموارد البشري حتى يكون تنفيذه وفقا على التخطيط وتحقيق الأهداف بفعالة. الكلمات المفاتحية : الإدارة، تخطيط البرنامج، تعليم اللغة العربية